Cognitive radio wireless networks - Joyantee, Tasnia Jahed; Iqbal, Niaz; Das, Ipshita (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.